Expressão e purificação de proteínas recombinantes do organismo modelo Neurospora crassa - Matsuno, Guilherme Eiji [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Model organisms are those considered representatives to fundamental attributes of the kingdoms of organisms or even life itself. Among model organisms, the early works of George W. Beadle and Edward L. Tatum with the fungus Neurospora crassa stimulated the use of microorganisms and has initiated a new era, combining genetics and biochemistry. The fungus N. crassa is easy to grow, showing greater morphological and developmental complexity due to its multicellular characteristics. Moreover, many proteins are predicted as similar proteins in animals, plants and other filamentous fungi. This information emphasizes the potential of N. crassa as a model for elucidation of still unknown biochemical and genetic mechanisms. However, 41% of the analyzed proteins are related to known proteins. Another 30% are hypothetical proteins with no similarity to proteins deposited in databases. Among metabolic pathways targets of studies in Neurospora, an interesting feature is the glycogen metabolism. Under stress conditions, the temperature (heat shock), the glycogen concentration decreases, while in yeast the behavior is opposite. Thus, studies have identified proteins involved in these pathways. The Importin-α protein is important because of its role in recognizing proteins to be transported from the cytoplasm to the cell nucleus. Its study is important as it participates in the transport of proteins involved in the regulation of glycogen metabolism. Another protein is NCU03482, which is identified as a helicase RuvB-like protein, which is responsible for the remodeling of chromatin in human protein. In this work, the expression and purification of recombinant protein Importin-α (Imp-α) and NCU03482 were performed, and the circular dichroism experiment with the sample of Imp-α. Results indicate that the proteins were expressed in Escherichia coli successfully, as well as purification of them. However, among the proteins, the Imp-α was obtained in a...

Organismos modelos são aqueles considerados representantes para atributos fundamentais dos reinos dos organismos ou mesmo da própria vida. Dentre os organismos modelo, os primeiros trabalhos de George W. Beadle e Edward L. Tatum com o fungo Neurospora crassa estimularam o uso de microorganismos e foi dado início a uma nova era, unindo genética e bioquímica. O fungo N. crassa é de fácil cultivo, apresentando maior complexidade morfológica e de desenvolvimento devido as suas características multicelulares. Além disso, muitas proteínas preditas são semelhantes às proteínas em animais, plantas e outros fungos filamentosos. Essas informações reforçam o potencial de N. crassa como modelo para elucidação de mecanismos bioquímicos e genéticos ainda desconhecidos. No entanto, 41% das proteínas analisadas são relacionadas com proteínas conhecidas. Outros 30% correspondem a proteínas hipotéticas sem semelhanças com proteínas depositadas em bancos de dados. Dentre as vias metabólicas alvo de estudo em Neurospora, uma característica interessante é o metabolismo do glicogênio. Sob condições de estresse a temperatura (heat shock), a concentração de glicogênio diminui, enquanto em leveduras o comportamento é oposto. Dessa maneira, estudos identificaram proteínas envolvidas nessas vias. A proteína Importina-α é importante devido ao seu papel de reconhecer proteínas a ser transportadas do citoplasma para o núcleo celular. Seu estudo é importante pois participa de transporte de proteínas envolvidas na regulação do metabolismo do glicogênio. Outra proteína é a NCU03482, a qual encontra-se identificada como proteína semelhante a helicase RuvB, que é responsável pela remodelagem da cromatina em humanos. Nesse trabalho, foram realizadas a expressão e purificação das proteínas recombinantes Importina-α (Imp-α) e NCU03482, bem como o experimento de dicroísmo circular com a amostra de Imp-α. Resultados indicam...
Keywords: Neurospora crassa; Proteínas recombinantes; Dicroismo circular; Analise cromatografica; Proteinas - Pesquisa; Circular dichroism